Learning What Works in Sensory Disabilities: Establishing Causal Inference. (November 2015) - Cooney, John B.; Young, John; Luckner, John L.; Ferrell, Kay Alicyn
This article is intended to assist teachers and researchers in designing studies that examine the efficacy of a particular intervention or strategy with students with sensory disabilities. Ten research designs that can establish causal inference (the ability to attribute any effects to the intervention) with and without randomization are discussed.